The importance of two-sided heterogeneity for the cyclicality of labour market dynamics - Ronald Bachmann; Peggy Bechara (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2018)
Using administrative data on individual workers' employment history and firms, we investigate the cyclicality of worker flows on the German labour market. Focusing on heterogeneities on both sides of the labour market, we find that small firms hire much more workers from unemployment than large firms, and that they do so at the very beginning of an economic expansion. Later on in the expansion, overall hirings more frequently result from direct job-to-job transitions to larger firms. Transitions from unemployment to employment at large firms are generally found to be more (pro-)cyclical. However, this stylised fact disappears when the composition of the workforce is controlled for.
Keywords: J63; J64; J21; E24; 330; worker flows; accessions; hirings; separations; business cycle; job-to-job; employer-to-employer